Seismic velocity anomalies in the infilling of tunnel valleys: influence on the interpretation of seismic data. An example from western Lithuania - Gerok, Dmitrij; Kaminskas, Donatas; Gibbard, Philip (GFF, 2017)
Buried tunnel valleys, developed by glacial meltwater below former continental ice-sheets, are often hardly recognisable during deep land seismic surveys and may act as obstructions in the investigation of deeper geological strata both onshore and offshore. Unique, detailed high-resolution onshore seismic investigations in western Lithuania revealed strong or marked anomalies of seismic velocities within the infilling of a tunnel valley. Such an anomaly produces a pull-up effect of seismic reflections from deeper geological interfaces, which in turn may produce inaccuracies in seismic data interpretation giving false pull-up structures, false faults and even false oil traps. In this paper, a method for improving depth mapping of horizons subject to high-velocity pull-ups in time-domain images is discussed. Using seismic and well-log data, improved geological sections were obtained by properly accounting for seismic velocities of valley-infill (lenses) obtained via well-logs.